The Birthday Room - Henkes, Kevin (New York Greenwillow Books, 1999)
When twelve-year-old Ben visits his uncle in Oregon, he feels caught in the strained relationship between his mother and her brother while he also begins to accept himself as an artist.
5 - 9
Keywords: Family life - Fiction; Uncles - Fiction; Self-acceptance - Fiction